Epithelial ultrastructure and cellular mechanisms of acid and base transport in the Drosophila midgut. - Shanbhag, S.; Tripathi, S. (Journal of Experimental Biology, 2009)
There is a resurgence of interest in the Drosophila midgut on account of its potential value in understanding the structure, development and function of digestive organs and related epithelia. The recent identification of regenerative or stem cells in the adult gut of Drosophila has opened up new avenues for understanding development and turnover of cells in insect and mammalian gastrointestinal tracts. Conversely, the physiology of the Drosophila gut is less well understood as it is a difficult epithelial preparation to study under controlled conditions. Recent progress in microperfusion of individual segments of the Drosophila midgut, in both larval and adult forms, has enabled ultrastructural and electrophysiological study and preliminary characterization of cellular transport processes in the epithelium. As larvae are more active feeders, the transport rates are higher than in adults. The larval midgut has at least three segments: an anterior neutral zone, a short and narrow acid-secreting middle segment and a long and wider posterior segment (which is the best studied) that secretes base (probably HCO(3)(-)) into the lumen. The posterior midgut has a lumen-negative transepithelial potential (35-45 mV) and a high resistance (800-1400 Omega.cm(2)) that correlates with little or no lateral intercellular volume. The primary transport system driving base secretion into the lumen appears to be a bafilomycin-A(1)-sensitive, electrogenic H(+) V-ATPase located on the basal membrane, which extrudes acid into the haemolymph, as inferred from the extracellular pH gradients detected adjacent to the basal membrane. The adult midgut is also segmented (as inferred from longitudinal gradients of pH dye-indicators in the lumen) into anterior, middle and posterior regions. The anterior segment is probably absorptive. The middle midgut secretes acid (pH<4.0), a process dependent on a carbonic-anhydrase-catalysed H(+) pool. Cells of the middle segment are alternately absorptive (apically amplified by approximately 9-fold, basally amplified by >90-fold) and secretory (apically amplified by >90-fold and basally by approximately 10-fold). Posterior segment cells have an extensively dilated basal extracellular labyrinth, with a volume larger than that of anterior segment cells, indicating more fluid reabsorption in the posterior segment. The luminal pH of anterior and posterior adult midgut is 7-9. These findings in the larval and adult midgut open up the possibility of determining the role of plasma membrane transporters and channels involved in driving not only H(+) fluxes but also secondary fluxes of other solutes and water in Drosophila.